WANITA: ANTARA KARIER POLITIK DAN BUDAYA POLITIK DI INDONESIA - Handayani, Trisakti (Jurnal Bestari, 1994)
In the several countries, women's position has existed. For instance Margareth Thatcher (United Kingdom), Corey Aquino (Philippine), and Benazir Bhuto (Pakistan) etc. They can be seen as one of indicators of women's roles and leaderships. Moreover, they have come before and led the public not to be caused by this femaleness but by their capacities and qualities to lead the country.